A Comparative Study of Two Anesthetic Agents Thiopentone Sodium and Propofol in Modified Electroconvulsive Therapy - Sanagapalli S. V. L. Manasa; E. Ananda Reddy; V. Harshitha; Velama Pooja Prasanna; Chennuru Kavya Lekha; Javangula Swetha Krishna (Taiwanese Journal of Psychiatry)
Objectives: Modified electroconvulsive therapy (MECT) remains one of the effective treatment modalities for various psychiatric illnesses. There are various anesthetic agents used in MECT. Thiopentone sodium and propofol are the most commonly used induction agents but differences exist among these two agents. In this study, we intended to compare thiopentone sodium and propofol in seizure duration, recovery time, hemodynamic, and cognitive profiles in patients receiving MECT. Methods: This was a comparative study done in Narayana Medical College and Hospital, Nellore, Andhra Pradesh, India. We recruited 80 study patients who were diagnosed with severe depression with suicidal ideations and schizophrenia with positive symptoms and were planned for receiving MECT. The study patients received assessments using Hamilton Rating Scale for depression (HAM-D), Positive and Negative Syndrome Scale, and Brief Cognitive Rating Scale (BCRS) at the time of admission, after the first, and the last post-MECT sessions. Results: The difference of the mean seizure duration between in thiopentone sodium and propofol (28.3 vs. 20.9 s) was statistically significant (p < 0.01). There were significant changes in baseline parameters after the procedure. The difference in the mean value of the recovery period between the thiopentone sodium and propofol group, i.e., (467.0 ± 72.2 vs. 311.5 ± 58.6 s) was also significant (p < 01). The mean BCRS scores after 1st and last sessions in the thiopentone sodium group were 9.2 and 11.6, respectively, whereas those in the propofol group were 8.0 and 10.0, respectively. The mean BCRS scores between the first and the last post-MECT were significantly different in the thiopentone sodium group (p < 0.01) and the propoful group (p < 0.01). The mean BCRS scores were significantly different at the first post-MECT (p < 0.05) and the last post-MECT (p < 0.05) between two anesthetic groups. Conclusion: The study showed that propofol was a better anesthetic agent than thiopentone sodium as propofol had faster recovery time with stable hemodynamic parameters, and less cognitive deficits, but had shorter seizure duration.